Comparative effectiveness of first‐line radiofrequency ablation versus surgical resection and transplantation for patients with early hepatocellular carcinoma. Issue 10 (13th January 2017) - Kutlu, Onur C.; Chan, Jennifer A.; Aloia, Thomas A.; Chun, Yun S.; Kaseb, Ahmed O.; Passot, Guillaume; Yamashita, Suguru; Vauthey, Jean‐Nicolas; Conrad, Claudius
Abstract : BACKGROUND: Significant controversy exists as to which treatment modality is most effective for small, solitary hepatocellular carcinomas (HCCs): radiofrequency ablation (RFA), surgical resection (RXN), or transplantation (TXP). Size cutoff values ranging from 20 to 50 mm have been proposed to achieve complete ablation. The current study compares outcomes between RFA, RXN, and TXP as first‐line therapy for patients with HCC tumors measuring as large as 50 mm. METHODS: The Surveillance, Epidemiology, and End Results database was queried for patients with HCC tumors measuring up to 50 mm who were treated with RFA, RXN, or TXP between 2004 and 2013. Overall survival (OS) and disease‐specific survival (DSS) were examined in patients with tumors measuring ≤20 mm, 21 to 30 mm, or 31 to 50 mm. The impact of an increase in tumor size of only 5 mm beyond 30 mm was evaluated by also examining outcomes in patients with tumors measuring 31 to 35 mm. RESULTS: Of 1894 cases, patients with HCC tumors measuring ≤20 mm and 21 to 30 mm demonstrated no difference in OS or DSS regardless of whether RFA and RXN was used. RFA was associated with a worse OS and DSS than TXP, whereas there was no difference in OS observed between RXN and TXP. In patients with tumors measuring 31 to 50 mm, OS and DSS were worse with RFA compared with RXN or TXP. Most important, the inferior DSS and OS noted with RFA were observed with only a 5‐mm increase in tumors measuring >30 mm. CONCLUSIONS: Although RFA frequently is used as first‐line treatment of HCC tumors measuring as large as 50 mm, it is associated with worse results than RXN or TXP for tumors measuring >30 mm. To the best of the authors' knowledge, the results of the current study are the first to demonstrate that although RFA is an appropriate option for patients with HCC tumors measuring ≤30 mm, its use for tumors even slightly larger than 30 mm is associated with inferior outcomes. Cancer 2017;123:1817–1827 . © 2017 American Cancer Society . Abstract : While a significant number of hepatocellular carcinoma (HCC) greater than 3cm in the US are treated with radiofrequency ablation (RFA), RFA is associated with worse outcomes as first‐line therapy when applied to tumors >3cm. Increasing the size indication by 5mm only to HCC of 35mm leads to significantly worse survival; however, RFA is an appropriate alternative for HCC <3cm with comparable outcomes to resection and ablation.